Enhanced superconducting properties and microstructures of Y0.5Gd0.5B2C3O7-δ/ LaGdZr2O7/ Y0.5Gd0.5Ba2Cu3O7-δfilm. Issue 16 (November 2020) - Zheng, Tong; Wang, Wei; Liu, Linfei; Liu, Shunfan; Li, Yijie
Abstract: Thickness effect severely limits the performance of REBa2 Cu3 O7-δ coated conductors. In this work, a Y0.5 Gd0.5 B2 C3 O7-δ /LaGdZr2 O7 /Y0.5 Gd0.5 Ba2 Cu3 O7-δ (YGdBCO/LGZO/YGdBCO) tri-layer film was fabricated by pulse laser deposition, which successfully inhibited the thickness effect and improved the superconductivity of YGdBCO film. By investigating the microstructure of the inserted LGZO layer, it was found that LGZO interlayer can not only reduce the surface roughness of the bottom YGdBCO layer by inhibiting the continuous growth of YGdBCO crystal grains but also realize the transmission of current between superconducting layers. With the deposition of LGZO interlayer, the critical current of the YGdBCO film increased significantly by nearly 50% from 180 A of a double-layer YGdBCO film with the same thickness to 270 A. Transmission Electron Microscope (TEM) observation and Energy Dispersive Spectroscopy (EDS) analysis indicate that the incomplete oxidized particles in the LGZO layer serve as the current channels between YGdBCO layers in the samples prepared at a laser energy of more than 210 mJ.